Analisis Kekuatan, Kelemahan, Peluang, dan Ancaman Usaha Bengkel Karel Wairhubing, Kabupaten Sikka - Theresia Yunivita Ertilia; Emilianus Eo Kutu Goo; Veronika Toa; Benediktius Te Basa; Yohanes Kristo Doke; Margareta Valencia Custodi; Denisco Vanstefen Naga Costa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the internal and external conditions of Karel Workshop in Wairhubing, Sikka Regency, using a SWOT approach (Strengths, Weaknesses, Opportunities, and Threats) as a basis for formulating business development strategies. The research employed a qualitative descriptive method with data collected through in-depth interviews with the owner, employees, and customers, as well as secondary data from documents and official statistics. The findings indicate that Karel Workshop possesses several strengths, including meticulous service quality, strong interpersonal relationships with customers, and mechanic skills acquired through self-learning. However, the workshop also faces weaknesses such as limited equipment, the absence of a structured management system, and a lack of digital promotion. Opportunities that can be utilized include high public interest in motorcycle modification, potential motorcycle painting services, a strategic location, and possible partnerships with spare-part suppliers. Meanwhile, the main threats include rising spare-part prices, competition among workshops, and occupational safety risks. Overall, the study recommends strengthening digital promotion, improving business management, enhancing workshop facilities, and implementing safety standards to support the sustainable development of Karel Workshop.